1992
DOI: 10.1002/bimj.4710340303
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical and Simulated Comparison of Some Tests for Detecting Progressiveness of Response with Increasing Doses of a Compound

Abstract: summaryExperiments consisting of several doses of a test agent and a zero dose control are often conducted to evaluate the effect of a compound on the response of interest.et al. (1985) proposed a trend test procedure which uses the minimum pvalue from three candidate dose scalings as a sensitive means for detecting a trend in response with increasing dose. Trend is defined here as a progressiveness, either increasing or decreasing, in response with increasing dose of the test agent. In this paper, we take a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…For the primary endpoint (assessment of mineralization) a two-sided trend test (18,19) was used to evaluate differences among the treatment groups within each of the osteoporosis studies at a particular timepoint.…”
Section: Histomorphometrymentioning
confidence: 99%
“…For the primary endpoint (assessment of mineralization) a two-sided trend test (18,19) was used to evaluate differences among the treatment groups within each of the osteoporosis studies at a particular timepoint.…”
Section: Histomorphometrymentioning
confidence: 99%
“…Similar to Capizzi et al (1992), we consider the following expected mean response at each center and each dose level:…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Tukey, Ciminera, and Heyse (1985) proposed a regressionbased procedure for assessing a trend in response with increasing dose of a compound and for comparing each dose with the control in a stepwise fashion in a one-way design. Capizzi et al (1992) suggested an adjusted trend test procedure that controlled the inflated Type I error observed with the Tukey et al (1985) approach. In this paper, we propose an extension of the adjusted trend test that is suitable for multicenter clinical trials and has less restrictive assumptions than existing approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The actions which should be taken by various procedures are as in the table. Procedure (3 ) of both versions reject more hypotheses than Procedures (1 ) and (2 ). The regular Bonferroni procedure rejects H 11 , and the regular Hochberg procedures rejects H 11 and H 21 .…”
Section: Examplementioning
confidence: 90%
“…A well designed closed testing procedure has been shown to have much more power than the traditional Bonferroni procedure. For a trial with the primary objective to assess the dose-response relationship of multiple doses of an active treatment versus a placebo control on one primary endpoint, the stepdown trend tests [1][2][3][4] are natural closed testing procedures for comparing each dose to the placebo control. These stepdown trend test procedures assume an ordered restriction on the mean responses according to the dose levels.…”
Section: Introductionmentioning
confidence: 99%